Perkembangan Bahasa Ekspresif Anak dengan Gangguan Specific Language Impairment (SLI) melalui Penerapan Metode Bernyanyi - Ruth Donda E. Panggabean; Mei Lyna `Girsang; Joanna Andre Neelce Angela B (Journal on Education, 2023)
The purpose of this research is to develop expressive language in children aged five years who experience Specific Language Impairment disorders through the method of singing. This type of research is descriptive research. The research subject initials AT, a boy who was declared to have a Specific Language Impairment (SLI) disorder after undergoing an assessment from a licensed psychology institute. SLI disorders experienced by AT are caused by brain injury due to collision on his head when AT was 8 months old. The pleasure of AT in humming or singing is used as a method in developing the expressive language of AT which has not developed according to its age. Based on the results of initial observations, when given a question AT answered with one word that is not clear, or repeat the word heard from his friend, even sometimes AT does not answer. The development of the expressive language AT described based on indicators spoken verbally with their own language, answering simple questions, receiving and conveying simple messages, speaking fluently using complex sentences consisting of 5-6 words. The application of singing method by using media and the openness of parents to get involved produces expressive language development very rapidly.